ҚАРАҚАЛПАҚ ЖЫРАЎШЫЛЫҚ ӨНЕРИ ҲӘМ ШАҢҚАЙ ЖЫРАЎ ДӨРЕТИЎШИЛИГИ - Эгамкулова, Г.М. (FAN va JAMIYAT, 2022)
This article provides some information about the Karakalpak jiravic craft, well-known jiravs who lived and worked in Bukhara and Navoi regions. The life, work and literary heritage of Shanghai Zhirov, who lived and worked in the XIX century, are analyzed.